A reliable unipedal stance test for the assessment of balance using a force platform - Ponce-Gonzalez, J. G.; Sanchis-Moysi, J.; González-Henriquez, J. J.; Arteaga-Ortiz, R.; Calbet, J. A. L.; Dorado, C. (The Journal of Sports Medicine and Physical Fitness, 2014)
BACKGROUND: The aim was to develop a unipedal stance test for the assessment of balance using a force platform.